Miniaturized High-Isolation Dual-Frequency Orthogonally Polarized Patch Antenna Using Compact Electromagnetic Bandgap Filters. (17th April 2014) - Cheng, Chunxia; Zhang, Fushun; Wan, Yangtao; Zhang, Fan
Abstract : A miniaturized dual-frequency dual-polarization microstrip patch antenna with high isolation between receiving and transmitting ports (operating at 2.1 GHz for receiving and at 2.5 GHz for transmitting) is presented in this paper. The proposed antenna consists of a modified rectangular radiating patch, two 50 Ω microstrip feed lines, and two EBG filters. Two coupling microstrip lines are employed to excite two orthogonal fundamental modes (TM10 and TM01 ). The high isolation is achieved by embedding two novel EBG filters underneath two feed lines to reject the incoming signal from the opposite line. Multilayer configuration, miniaturized EBG filters, and modified rectangular radiation patch contribute to size reduction. The total size is 0.67λ × 0.67λ × 0.03λ , only quarter of the multilayer rectangular radiation patch antenna (1.33λ × 1.33λ × 0.03λ ) using common EBG filters with the same performance. Measured results on the reflection coefficients, isolations, and gains for the two frequencies are provided, which agree well with the numerical simulations. Also, measured isolations and radiation patterns at both two resonant frequencies are compared with the antenna without filters. The results show that the proposed method improves isolation by more than 20 dB with little influence on the radiation patterns.